A neonicotinoid pesticide impairs foraging, but not learning, in free-flying bumblebees - Muth, F. (Sci Rep, 2019)
Neonicotinoids are widely-used pesticides implicated in the decline of bees, known to have sub-lethal effects on bees’ foraging and colony performance. One proposed mechanism for these negative effects is impairment to bees’ ability to learn floral associations. However, the effects of neonicotinoids on learning performance have largely been addressed using a single protocol, where immobilized bees learn an association based on a single sensory modality. We thus have an incomplete understanding of how these pesticides affect bee learning in more naturalistic foraging scenarios. We carried out the first free-foraging study into the effects of acute exposure of a neonicotinoid (imidacloprid) on bumblebees’ (Bombus impatiens) ability to learn associations with visual stimuli. We uncovered dose-dependent detrimental effects on motivation to initiate foraging, amount of nectar collected, and initiation of subsequent foraging bouts. However, we did not find any impairment to bees’ ability to learn visual associations. While not precluding the possibility that other forms of learning are impaired, our findings suggest that some of the major effects of acute neonicotinoid exposure on foraging performance may be due to motivational and/or sensory impairments. In light of these findings, we discuss more broadly how pesticide effects on pollinator cognition might be studied.